THE MODEL OF FORMATION OF FUTURE FOREING LANGUAGE TEACHER’S POLYCULTURE - Zabolotska, Olga (Revista Inclusiones, 2020)
This article deals with the problem of formation of future language teachers’ polyculture in the condition of polylingual educational environment. Structural and functional model of the formation of future language teachers’ polyculture was elaborated for proving the effectiveness of the research’s hypothesis. This model includes target, processual, content, control components and monitoring of results that gives an opportunity to demonstrate the main approaches, principles, methods and means of its implementation in educational process. The dominant approaches for our research are: competitive, communicative and cognitive, integrative, individual and activity, cultural. Among general didactic principles there were defined the following: students’ activity while studying, systemacy, consistency in acquiring knowledge and development of skills, individualization, individual work of students while studying through the content of professionally oriented disciplines; and methodical principles: situations of studying process, intercultural domination of studying interactivity, priority of tasks and polyfunctionality of tasks, dialogue of cultures, co-studying of foreign language with foreign culture.